2016
DOI: 10.5539/ijbm.v11n9p281
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Performance Appraisal on Employees’ Job Satisfaction and Organizational Commitment: A Case of Microfinance Institutions in Ghana

Abstract: Performance appraisal is credited by researchers as a tool for spurring employees towards the attainment of organizational goals. Considering employees' attitudes as a vital component in the attainment of organizational goals, this study investigated the impacts of performance appraisal on the job-satisfaction and commitment of employees. The study used a descriptive research design. A stratified random sampling was used to sample 200 respondents from Microfinance organizations in Ghana. The study used questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
6
23
0
Order By: Relevance
“…Administrators will use the assessment methods to determine the employees' performance scores and recommend the types, level and or amount of pay that is consistent or commensurate with the level achievements performed by the employees. The ability of administrators to equally allocate pay-wage according to employee achievements may strongly motivate them to respect and accept their organisational merit pay objectives (Agyare, Yuhui, Mensah, Aidoo & Ansah 2016;Munir, Aziz, Shaladin & Muhammad 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Administrators will use the assessment methods to determine the employees' performance scores and recommend the types, level and or amount of pay that is consistent or commensurate with the level achievements performed by the employees. The ability of administrators to equally allocate pay-wage according to employee achievements may strongly motivate them to respect and accept their organisational merit pay objectives (Agyare, Yuhui, Mensah, Aidoo & Ansah 2016;Munir, Aziz, Shaladin & Muhammad 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They should put in mind that commitment is not only related to the fairness of performance appraisal exercises, it is also positively related to employee involvement in the formulation of appraisal tools, clarity of purpose of performance appraisals to employees, and an appreciation of the relevance of evaluation criteria by employees (Agyare et al,2016). When academic employees perceive that they are not allowed authentic participation or not taken seriously, they tend to have negative dispositions towards the management (Sagie and Aycan, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…This study concluded both the factors significantly influencing the performance management system. The implementation and assessment procedure of the performance of the employees is necessary to identify the productivity and its effects in an organization in a better way (Agyare et al, 2016). The understanding and learning of organizations goals and vision by employees is important to perform well in the organisation.…”
Section: Review Of Literaturementioning
confidence: 99%